2011
DOI: 10.1002/ptr.3562
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Aucubin on H2O2‐Induced Apoptosis in PC12 Cells

Abstract: The present study investigated the neuroprotective effects of aucubin on hydrogen peroxide (H₂O₂)-induced apoptosis in PC12 cells. Exposure of PC12 cells to 0.25 mm H₂O₂ induced a leakage of lactate dehydrogenase and decreased cell viability, as shown by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. In a dose over 0.1 mm, aucubin increased PC12 cellular viability and markedly attenuated H₂O₂-induced apoptotic cell death. Quantitation of apoptosis by flow cytometry indicated that aucubin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Thus, removing hydroxyl radical is very 297 important for the protection of living systems (Luo, Fan & Luo, 2011 (Nordberg & Arner, 2001), H 2 O 2 has been used in many studies to trigger cell 308 apoptosis (Tang et al, 2005). Antioxidants could prevent PC12 cell death through the 309 suppression of H 2 O 2 -induced ROS formation (Guan, Bao, Jiang & An, 2006), and 310 regulate the endogenous oxidant-antioxidant balance (Xue, Gao, Lin, Jin & Xu, 2012). and it acts as a cytotoxic agent in pathological processes, an inducer or suppressor of 341 apoptosis and an immunoregulator (Coleman, 2001).…”
mentioning
confidence: 99%
“…Thus, removing hydroxyl radical is very 297 important for the protection of living systems (Luo, Fan & Luo, 2011 (Nordberg & Arner, 2001), H 2 O 2 has been used in many studies to trigger cell 308 apoptosis (Tang et al, 2005). Antioxidants could prevent PC12 cell death through the 309 suppression of H 2 O 2 -induced ROS formation (Guan, Bao, Jiang & An, 2006), and 310 regulate the endogenous oxidant-antioxidant balance (Xue, Gao, Lin, Jin & Xu, 2012). and it acts as a cytotoxic agent in pathological processes, an inducer or suppressor of 341 apoptosis and an immunoregulator (Coleman, 2001).…”
mentioning
confidence: 99%
“…Previously, the effect of aucubin on PC12 cells has been shown in a wide range of concentration. Cell viability in H 2 O 2 -treated PC12 cells was increased under concentrations of about 50~400 µg/ml (0.1 to 1 mM) aucubin [8, 9], but their neurites were elongated under 0.1 to 1 µg/ml aucubin [11]. However, these studies did not examine any differentiation markers.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that relatively high concentrations of aucubin (0.1 mM to 1 mM) have protective effects on H 2 O 2 -induced apoptosis in PC12 cells [8, 9]. There are reports that compound VI containing natural lignans and iridoid, which includes partly glucosidase-hydrolyzed aucubin, promotes neuronal differentiation and lengthening neuritis of PC12h cells, a cultured cell line of paraneuron[10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that paclitaxel shows cytotoxicity by inducing oxidative stress. 26) This indicates that an antioxidant activity by aucubin [27][28][29] may attenuate paclitaxel-induced cytotoxicity that is mediated through oxidative stress.…”
Section: )mentioning
confidence: 99%